Plasma nitric oxide concentrations and erythrocyte arginase activities in lambs with contagious ecthyma - Kandemir, F. M.; Issi, M.; Benzer, F.; Gul, Y.; Basbug, O.; Ozdemir, N. (Ecole Nationale Veterinaire Toulouse, 2011)
The aim of the present study was to investigate the plasma nitric oxide concentrations and the erythrocyte arginase activities in lambs with contagious ecthyma, which frequently occurs in lambs and goat kids. The study was conducted on 10 Akkaraman, 1-2 month old lambs with contagious ecthyma (the clinical diagnosis was based on the presence of typical cauliflower-like proliferative lesions in lips, commissum labials, nostrils and udders) and on 10 apparently healthy lambs (controls) from the same flock. Plasma NO concentrations and erythrocyte arginase activities were determined on all animals using the Griess method and the thiosemicarbazide diacetylmonoxime urea (TDMU) method, respectively. Compared to the control group, the mean plasma NO concentration was significantly increased in the diseased group while the mean arginase activity was markedly depressed. Abnormally high NO concentrations and low enzyme activities were observed in 9 and 10 diseased lambs, respectively. Additionally, a negative correlation was evidenced between the 2 biochemical parameters. These results show that this viral infection is associated with some perturbations in the arginine metabolism, leading preferentially to the synthesis of NO, which is presumed to exhibit some antiviral properties.
Keywords: Lamb; contagious ecthyma; plasma; nitric oxide; erythrocyte; arginase